Perancangan Antena Helix Frekuensi 433 MHz Pita Lebar - Melvi, Melvi; Lestari, Fitri; Ulvan, Ardian; Aryanto, Aryanto; Batubara, Mona Arif Muda (Penerbit Goodwood, 2023)
Purpose: This research focuses on the design and analysis of a helix antenna operating at 433 MHz with a 4 MHz bandwidth. This study aims to investigate the antenna's performance and functionality with a focus on reception capabilities. Methodology: The research was conducted in two stages. First, the helix antenna was simulated based on predetermined parameters. The simulation process produced values such as return loss, VSWR, impedance, and gain. Afterward, the antenna was fabricated and tested using a Vector Network Analyzer (6000A) to verify the simulated values. The key measured parameters included return loss (-19.8866 dB), VSWR (1.22547), and impedance (46.5695 Ohms). A 1000 mW telemetry radio module was used as the transmission source during field testing. Results: The helix antenna showed a directional radiation pattern with a simulated gain of 9.231 dB. Field testing confirmed the antenna's functionality as a receiver, achieving a maximum transmission distance of 2.6 km. Signal strength was measured using the Received Signal Strength Indicator (RSSI). However, the data quality was not optimal due to environmental obstructions. Conclusion: There was minimal shift between simulated and measured parameters. However, the antenna's real-world performance was affected by interference and non-ideal outdoor conditions. Limitations: Testing was conducted in areas with suboptimal line-of-sight conditions, which impacted signal strength and introduced interference. Contribution: This study enhances the understanding of helix antennas for receiver applications at 433 MHz and provides valuable insights into performance under practical conditions.